The formation and evolution of Titan's winter polar vortex. Issue 1 (December 2017) - Teanby, Nicholas; Bézard, Bruno; Vinatier, Sandrine; Sylvestre, Melody; Nixon, Conor; Irwin, Patrick; Kok, Remco; Calcutt, Simon; Flasar, F.
Abstract Saturn's largest moon Titan has a substantial nitrogen-methane atmosphere, with strong seasonal effects, including formation of winter polar vortices. Following Titan's 2009 northern spring equinox, peak solar heating moved to the northern hemisphere, initiating south-polar subsidence and winter polar vortex formation. Throughout 2010–2011, strengthening subsidence produced a mesospheric hot-spot and caused extreme enrichment of photochemically produced trace gases. However, in 2012 unexpected and rapid mesospheric cooling was observed. Here we show extreme trace gas enrichment within the polar vortex dramatically increases mesospheric long-wave radiative cooling efficiency, causing unusually cold temperatures 2–6 years post-equinox. The long time-frame to reach a stable vortex configuration results from the high infrared opacity of Titan's trace gases and the relatively long atmospheric radiative time constant. Winter polar hot-spots have been observed on other planets, but detection of post-equinox cooling is so far unique to Titan. The polar hot-spot appeared in Titan after equinox in 2010 suddenly cooled in early 2012, which wasn't predicted by models. Here the authors use observations to show that the increase in trace gases during the hot-spot resulted in radiative cooling feedback.